81.9k views
5 votes
Simplify (1 − sin x)(1 + sin x).
A) 1
B) cos2 x
C) sin2 x
D) tan2 x

2 Answers

1 vote

Simplify (1 − sin x)(1 + sin x).

Answer:

B - cos2 x

User Bocajim
by
5.3k points
2 votes

Answer: optiob B.

Explanation:

Remember that:


cos^2x+sin^2x=1

Then, having the expression
(1-sinx)(1+sinx), apply distributive property. Then:


=1+sinx-sinx-sin^2x

Now you need to add the like terms:


=1-sin^2x

If you solve for
cos^2x from
cos^2x+sin^2x=1, you get:
cos^2x=1-sin^2x. Therefore the answer is:


=cos^2x

User Ekkis
by
4.8k points